Reconstruction of Learning Identity among International Students in Indonesian Islamic Higher Education - Rois Imron Rosi; Najiyya Najat Azzeehavella; Dina Alfiyah; Geritza Rabbani Setiawan (Institut Agama Islam Negeri Palangka Raya, 2026)
The study of learning identity is essential for ensuring students’ academic adjustment and success, as identity is widely recognized as a pivotal factor in educational outcomes. Scholars generally agree that identity is dynamic and changes over time; therefore, identity studies need to be continuously revisited. Although many studies have examined identity reconstruction among international students, limited attention has been paid to their learning identity. This study addresses this pedagogical gap by examining the reconstruction of learning identity among international students in Indonesian Islamic higher education, specifically at Maliki Islamic University, Malang. Using a qualitative phenomenological design, this study explored the experiences of 14 international students from various countries. Data were analyzed using thematic analysis. The findings identified four initial learning identity themes: individual, writing-based, book-based, and critical thinking and discussion-based learning identities. These identities were then reconstructed into two new learning identities to meet the demands of Indonesian learning practices: social-individual learning identity and digitally literate learning identity. Participants reported that adaptation generally occurred during the first year of study. During this period, they encountered several challenges, including culture shock and linguistic barriers. Beyond its theoretical contribution to studies on international students, this study offers practical insights for stakeholders seeking to establish a conducive and supportive academic environment that facilitates improved learning outcomes.